Measuring the Enterprise Green Innovation Strategy Decision-Making Quality: A Moderating—Mediating Model - Feng, Jiaying; Pan, Ying; Zhuang, Wencan (Frontiers in Psychology, 2022)
Green development helps to balance the conflict between economic expansion, environmental protection, and green strategy decisions by tackling the issue of excessive resource utilization during regional growth. This study aims to measure the green innovation strategic decisions quality by identifying the nexus between board capital, green innovation strategic information acquisition capability, and board group Faultline. A conceptual model has been proposed and tested to verify the proposed relationship. Data collection was analyzed using structural equation modeling in AMOS 24.0. The findings indicate that board human capital (BHC) and board social capital (BSC) have a beneficial influence on the quality of green innovation strategy decision-making. The green innovation strategic information acquisition capability plays a mediating role in the relationship between the two dimensions of board capital and the green innovation strategy decision-making quality. The mediating role of green innovation strategic information acquisition capability is moderated by board group Faultline. The core significance of this study is presented.